Entrepreneurship Training as well as Environmental Conservation for Junior High School Students through Ecoprint - Ratna Dewi; Tri Wiharti; Fadhillah Marta; Intan Oktaviani; Purwanto Agus (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
One of the P5 projects on the theme of entrepreneurship is Ecoprint, which is a natural batik art using plant parts as the basic material, and if done seriously, this batik art can generate income for its maker. The purpose of this service is to provide understanding through ecoprint training to students of SMP Muhammadiyah 1 Kartasura because of its relevance to the P5 subject on the theme of entrepreneurship. The method of this service is through lectures and direct practice of making ecoprints using both the hitting technique and the steaming technique. The results of the service show that there is an increase in the understanding of SMP Muhammadiyah 1 Kartasura students towards ecoprints, as well as the students' enthusiasm in making ecoprints. It can be concluded that this service activity went smoothly and the results of this service are expected to provide students with skills in developing an entrepreneurial spirit in the future. Keywords: Ecoprint, Entrepreneurship, P5, Training